Incidence of Stroke in Randomized Trials of COVID-19 Therapeutics: A Systematic Review and Meta-Analysis. Issue 11 (24th August 2022) - Nagraj, Sanjana; Varrias, Dimitrios; Hernandez Romero, Gabriel; Santos, Heitor T.; Karamanis, Dimitrios; Sagris, Dimitrios; Korompoki, Eleni; Milionis, Haralampos; Palaiodimos, Leonidas; Ntaios, George
Abstract : Background: COVID-19 has been frequently associated with an increased risk of thrombotic complications. There have also been reports of an increased likelihood of stroke, although its true incidence in patients with COVID-19 is currently unknown. Methods: Electronic databases PubMed and Scopus were searched from inception up to July 30, 2021 to identify randomized controlled studies in patients with confirmed COVID-19 undergoing one or more interventions. Studies were screened for eligibility using a predefined inclusion criterion and selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A random-effects model meta-analysis was conducted, and heterogeneity was assessed using I-squared test. Results: Out of 3960 potentially eligible articles, 77 randomized studies (38 732 patients) were included. Mean age of the study population was 55±9.3 years. Females constituted 38% of the study population and mean duration of follow-up after study enrollment was 23±12.9 days. Cumulative incidence of stroke in the overall study population was 0.001 (95% CI, 0.001–0.002) with a total of 65 events in 38 732 patients, corresponding to an absolute incidence of 0.168%. Incidence of stroke in the inpatient population was 0.001 (95% CI, 0.001–0.002; 65 events in 37 069 patients), corresponding to an absolute incidence of 0.175%. No strokes were observed in the outpatient setting. Conclusions: The overall incidence of stroke in patients with COVID-19 appears to be lower than that reported in previous observational reports.